CRISPR‐Cas9 technology and its application in haematological disorders. (13th September 2016) - Zhang, Han; McCarty, Nami
Summary: The recent advent of the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)‐CRISPR associated protein 9 (Cas9) system for precise genome editing has revolutionized methodologies in haematology and oncology studies. CRISPR‐Cas9 technology can be used to remove and correct genes or mutations, and to introduce site‐specific therapeutic genes in human cells. Inherited haematological disorders represent ideal targets for CRISPR‐Cas9‐mediated gene therapy. Correcting disease‐causing mutations could alleviate disease‐related symptoms in the near future. The CRISPR‐Cas9 system is also a useful tool for delineating molecular mechanisms involving haematological malignancies. Prior to the use of CRISPR‐Cas9‐mediated gene correction in humans, appropriate delivery systems with higher efficiency and specificity must be identified, and ethical guidelines for applying the technology with controllable safety must be established. Here, the latest applications of CRISPR‐Cas9 technology in haematological disorders, current challenges and future directions are reviewed and discussed.